Gastro-oesophageal reflux disease symptoms and tooth wear in patients with Sjögren’s syndrome - Wan Nik, Wan Noor Nazayan; Banerjee, Avijit; Moazzez, Rebecca (S. Karger AG, 2011)
The aim of this study was to assess the prevalence of gastrooesophageal reflux disease (GORD) symptoms and tooth wear in patients with Sjögren’s syndrome (SS) compared with matched controls. GORD symptoms were assessed for 33 SS patients and 20 age- and sex-matched controls. Tooth wear was assessed in all patients and controls. The results were further analysed in two subgroups of SS patients and controls with and without GORD symptoms (SS patients without GORD symptoms: n = 11, controls without GORD symptoms: n = 18). A higher proportion of SS patients reported suffering from heartburn and regurgitation than controls (p < 0.001 and p = 0.02, respectively). SS patients without GORD symptoms had a statistically significantly higher percentage of surfaces with tooth wear affecting dentine than controls (p < 0.001).